The Politics of Reform in Islamic Family Law and Its Impact on Gender Equality - Doni Azhari; Asmuni Asmuni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The reform of Islamic family law represents a complex political arena where religious doctrines, state authority, and civil society interests intersect in shaping gender norms. This study examines the political dynamics underlying Islamic family law reform across several Muslim-majority countries and its implications for gender equality. By analyzing case studies from the Middle East, South Asia, and Southeast Asia, the research highlights how the success of legal reform is influenced by the power of state actors, the role of religious scholars, international pressure, and the strength of women’s movements. In many contexts, family law remains one of the few legal domains where patriarchal norms are legally entrenched, despite constitutional commitments to human rights. Conversely, countries like Morocco and Tunisia illustrate that meaningful reforms are possible through strategic political engagement and strong alliances between state institutions and civil society organizations. These progressive reforms have led to greater protection of women’s rights in areas, such as marriage, divorce, child custody, and inheritance. Nevertheless, reform efforts often face strong resistance from conservative groups who claim to defend the authenticity of Islam. This study concludes that Islamic family law reform is not merely a theological issue but a contested political struggle that shapes the trajectory of gender justice in contemporary Muslim societies. Therefore, reform strategies must be tailored to the socio-political context of each country, embracing a dynamic fiqh (Islamic jurisprudence) approach and ensuring the active participation of women in legislative processes.